2021
DOI: 10.1016/j.pcl.2020.07.014
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors for Severity in Children with Coronavirus Disease 2019

Abstract: The coronavirus disease 2019 (COVID-19) pandemic has affected hundreds of thousands of people. The authors performed a comprehensive literature review to identify the underlying mechanisms and risk factors for severe COVID-19 in children. Children have accounted for 1.7% to 2% of the diagnosed cases of COVID-19. They often have milder disease than adults, and child deaths have been rare. The documented risk factors for severe disease in children are young age and underlying comorbidities. It is unclear whether… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
106
0
3

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 115 publications
(114 citation statements)
references
References 78 publications
5
106
0
3
Order By: Relevance
“…A number of factors may account for those differences. Several studies have reported a variety of comorbidities including overweight, asthma and ethnic origin black or Asian, and minority ethnic (BAME) groups as risk factors for MIS-C ( 1 ). These conditions are independently associated with Vitamin D (vit D) deficiency and that could be a possible explication for higher MIS-C incidence in these children.…”
Section: Introductionmentioning
confidence: 99%
“…A number of factors may account for those differences. Several studies have reported a variety of comorbidities including overweight, asthma and ethnic origin black or Asian, and minority ethnic (BAME) groups as risk factors for MIS-C ( 1 ). These conditions are independently associated with Vitamin D (vit D) deficiency and that could be a possible explication for higher MIS-C incidence in these children.…”
Section: Introductionmentioning
confidence: 99%
“…Temporal and epidemiologic evidence suggests that MIS-C is strongly associated with SARS-CoV-2, though causality has not been confirmed [3]. Most cases of MIS-C have been RT-PCR negative but antibody positive, indicating prior infection [3,[5][6]. Interestingly, our case demonstrates a rapid progression of symptoms from the time the patient originally tested positive to the time she tested negative (with antibodies) two days later, in support of the theory that MIS-C is a postinfectious inflammatory immune dysregulation [3,[5][6].…”
Section: Discussionmentioning
confidence: 99%
“…28,30,31 Children could also develop intussusception and diabetic ketoacidosis. 28,32 A subset of pediatric patients also develop potentially fatal multisystem inflammation with features of shock and multiorgan failure, Kawasaki disease-like features, cytokine storm with increase in IL-6 levels, macrophage activation, increase in inflammatory markers such as C-reactive protein (CRP), ferritin, B-type natriuretic peptide, and troponin-T. 33,34 As noted previously, exaggerated immune response can be a key component of COVID-19 pathogenesis. The immune system undergoes significant changes from birth to adulthood, and the immune system of younger children is different from that of the older children who have similar immune system as the adults.…”
Section: Pathogenesis Of Sars-cov-2 Infectionmentioning
confidence: 98%